Long-term care reform and the labor supply of household members: Evidence from a quasi-experiment - Johannes Geyer; Thorben Korfhage (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Germany introduced a new mandatory insurance for long-term care in 1995 as part of its social security system. It replaced a system based on meanstested social welfare. Benefits from the long-term care insurance are not means tested and depend on the required level of care. The insurance provides both benefits in kind and cash benefits. The new scheme improved the situation for households to organize informal care at home. This was one goal of the reform since policymakers view informal care as a cost-saving alternative to formal care. This view however neglects possible opportunity costs of reduced labor supply of carers. We exploit this reform as a quasi-experiment and examine its effect on the labor supply of caregivers who live in the same household as the care recipient. We find strong negative labor market effects for men but not for women. We conduct a series of robustness tests and find results to be stable.
Keywords: J22; H31; I13; 330; labor supply; long-term care; long-term care insurance; natural experiment; quasi-experiment